New candidates in the differential diagnosis of malignant mesothelioma from benign mesothelial hyperplasia and adenocarcinoma; DARS2 and suprabasin - Ucer, Ozlem; Kocaman, Nevin (Churchill Livingstone, 2022)
Objectives: Malignant mesothelioma (MM) is a primary malignant tumour with a very bad prognosis, which develops from the mesothelial cells lining the serosal surfaces. Because MM can show a wide variety of histo-logical patterns and its cytomorphological features are quite extensive, it is often confused with lung adeno-carcinomas (LAC) and reactive mesothelial hyperplasia (RMH). The immunohistochemical examination method is the most useful method for discrimination. In this study, we aimed to determine the value of suprabasin and DARS2 markers in the differential diagnosis of RMH, MM and LAC. Methods: Thirty MM, 30 LAC and 30 RMH samples selected from the archive of Firat University Hospital Pa-thology Department Laboratory were included in this study. Suprabasin and DARS2 markers were applied to the samples immunohistochemically and their place in the differential diagnosis was examined. Results: Although DARS2 expression was observed in RMH, MM and adenocarcinoma samples, Suprabasin expression was only observed in adenocarcinoma. There was a significant difference between the groups in terms of DARS2 and Suprabasin expression. No suprabasin expression was detected in MM and RMH. Conclusion: Suprabasin and DARS2 may be proposed as new biomarkers to differentiate MM from LAC.
Keywords: Malignant mesothelioma; Lung adenocarcinoma; Immunohistochemistry; DARS2; Suprabasin